PENDIDIKAN RAMAH ANAK PERSPEKTIF HADITS NABI - Ali Mohtarom (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
The pattern of child - friendly education is actually creating a safe, comfortable, healthy, conducive environment, accepting all the shortcomings of children and respecting the potential of children. The principles of child - friendly schools are: non - vio lent, non - discriminatory, the best education for children, the right to grow and develop and respect for children's opinions. Islam has a perspective on friendliness towards children, which emphasizes the recommendation to be merciful to children. As menti oned in the hadith of the Prophet: